KAJIAN LITERATUR: IMPLEMENTASI MEDIA APLIKASI MEMBACA PERMULAAN UNTUK ANAK SEKOLAH DASAR RENTANG WAKTU 2019-2025 - Sugiarto, Deasy Renaningtyas; Isnaeni, Wiwi; Subali, Bambang; Widiarti, Nuni (Universitas Veteran Bangun Nusantara, 2025)
Reading skills are fundamental skills that students must master in order to follow learning well. In fact, there are still students who have difficulty reading in the upper grades. For this reason, it is necessary for teachers to complete students' reading skills. The purpose of this study was to determine the effect of early reading application media for elementary school children. The research method is a Systematic Literature Review (SLR) conducted using Google Scholar, Google Search, and Research Gate from journals published since 2019-2025. This research explores various technology-based applications used in early reading learning. These apps were developed to improve children's reading skills, focusing on engaging and interactive approaches that suit children's learning needs. The results showed that the apps were effective in increasing learners' motivation and reading skills. It can be concluded that the use of technology-based beginning reading applications is proven to be able to increase the motivation and reading skills of elementary school participants.